Acute Lymphocytic Leukemia with Bilateral Renal Masses Masquerading as Nephroblastomatosis - Poonam Thakore; Salim Aljabari; Curtis Turner; Tetyana L. Vasylyeva (Hindawi Limited, 2015)
Acute lymphoblastic leukemia (ALL) is the most common malignancy in the pediatric patient population. However, renal involvement as the primary manifestation of ALL is rare. We report a case of a 4-year-old boy with bilateral renal lesions resembling nephroblastic rests as the first finding of early stage ALL preceding hematological changes and subsequent classic clinical findings by two weeks. These renal hypodensities completely resolved after one week of induction chemotherapy. This case demonstrates that renal involvement can be the only initial presenting finding of leukemia. Children with lesions resembling nephroblastic rests need appropriate surveillance due to the risk of malignant disease.